Development of Adult Diapers Made From Banana Stem Powder For Elderly Patients In the Panti Werdha - Rahayu, Lutfi Dwi; Agus Khoirul Anam; Wiwin Martiningsih (Health Access Journal, 2025)
Background : Elderly is someone older than 60 years who experiences several changes. Elderly health problems not only lie in the aspect of chronic or degenerative diseases, but the susceptibility to infection is quite high. Urine and alvi incontinence are problems that are often suffered by the elderly. Natural resources that can be used to develop diapers to reduce skin irritation are banana stems which are processed into powder. Research Objective : this is to develop adult diapers made from banana stem powder for elderly patients. Research Methods : This research design is Research and Development, with research procedures using ADDIE. This research was conducted at Griya Sakinah Nursing Home with 2 respondents and 6 media experts on January 27 - March 15, 2025. The research instruments used were expert validation and field trials. Research Results : this shows that the feasibility of expert validators is 84.23% and respondents are 88.23%. The results of the assessment of adult diaper products made from banana stem powder have met the criteria of being very feasible to use to help elderly patients. Conclusion : It is hoped that this adult diaper product made from banana stem powder can be used as an alternative to prevent skin irritation in the elderly.